Bridging technology and pedagogy: How TPACK-based PBL shapes critical thinking in human anatomy education - Puspita, Laila; Asih, Dwi Nyaning Retno; Oktafiani, Raicha; Komarudin, Komarudin (Biosfer: Jurnal Pendidikan Biologi, 2025)
Critical thinking skills are pivotal in science education, enabling students to comprehend complex concepts, solve problems effectively, and excel in academic assessments. This study aims to determine the effect of TPACK-based PBL in improving students' critical thinking skills in human anatomy. Using a quasi-experimental design with unequal control groups, the study involved 60 students from two classes (experimental and control groups) in East Lampung, Indonesia. Data analysis via one-way ANOVA revealed a statistically significant difference between the groups (p < 0.001), with the experimental group demonstrating superior performance (mean score: 86.02 vs. 50.10). The large effect size (Cohen's d = 6.13) underscores the transformative potential of TPACK-PBL in fostering analytical reasoning and cognitive flexibility. The integration of digital tools within the PBL framework bridges pedagogical strategies, technology applications, and content mastery, enabling students to engage with authentic real-world problems. These findings align with constructivist theory, which emphasizes the active construction of knowledge through problem-solving contexts. These findings contribute to a new pedagogical model that synergizes TPACK and PBL, offering actionable insights for curriculum developers and educators seeking to foster critical thinking in complex biology topic.